Red light-triggered nucleic acid-templated reaction based on cyclic oligonucleotide substrates - Zozulia, Oleksii; Bachmann, Tobias; Deussner-Helfmann, Nina S.; Beierlein, Frank; Heilemann, Mike; Mokhir, Andriy (Chemical Communications, 2019)
A red light-triggered reaction based on cyclic oligonucleotide substrates that is accelerated over 30-fold by specific nucleic acid templates and generates a bright fluorescent probe was developed. We confirmed that this reaction is compatible with fluorescence correlation spectroscopy (FCS) thereby allowing detection of nucleic acids down to 1 nM.
CRIS-Team Scopus Importer:2019-09-17